Does Financial Literacy Has Greater Role in Achieving Stock Investment Performance of College Investors? - Risna Wijayanti; Himmiyatul Amanah Jiwa Juwita (International Journal of Tourism and Hospitality in Asia Pasific, 2024)
This research aims to integrate the perspectives of rationality and irrationality, which cannot be separated in capital market participants, especially young investors, in the decision-making process of stock investment. The research emphasizes whether financial literacy plays a significant role in investment performance. Additionally, overconfidence, considered a behavioral aspect, can act as an intermediary linking financial literacy and investment performance. Conducted on 77 students who invest in the investment gallery in Malang, using random sampling techniques, the research is an explanatory study with a quantitative approach through a questionnaire processed by SEM-PLS analysis using Smart PLS 3.0. The findings of this study highlight the positive influence of financial literacy on stock investment performance, while overconfidence was found to have a mediating effect on the relationship between financial literacy and stock investment performance. The characteristics of respondents who are young age with limited funds for stock investment lead to low expectations of returns, resulting in quick satisfaction and then affecting stock investment performance. Therefore, objective and appropriate decision-making approaches might not absolutely achieve success, as simple strategies such as behavioral biases or psychological factors can lead to optimal investment performance.